Swine Flu 2009, Morbidity and Mortality in a Sample of patients Admitted in Al-kindy Teaching Hospital - Oleiwi, Hamzah Qoneed; Kubba, Rushdi A.H.; Salman, Mohammed Abdulr Jabbar; Khazaal, Faris Abdul Kareem (AL-Kindy College Medical Journal, 2012)
Objective; swine flu is known to be caused by influenza A subtypes H1N1,H1N2, H2N3, H3N1, and H3N2, was first proposed to be a disease related to human flu during the 1918 flu pandemic, Iraq face the epidemic of 2009, many patients admitted to the medical word of alkindy teaching hospital, the clinical features were observed and managed according to WHO protocols.The aim of the study; is to asses some features of morbidity and mortality of swine flu epidemic admitted patients in 2009 in alkindy teaching hospital.Methods; A total 131 patients with suspected influenzaadmitted to Alkindy Teaching Hospital all complain offever more than 38c, sore throat with or without cough.The admitted patients are of two maingroups;a)seventeen secondary school pupils on theirreturn from US,b)one hundred fourteen patientsadmitted from October till end of December 2009.History ,clinical examination and routine investigationsfor all patient in addition to blood samples and swabsfrom nose and throat were taken and sent to the centrallab to test for H1N1 by PCR(real time).Results; fifty three (42%) of our patients found to have swine flu by positive test (real time PCR). It show that there is no relation of age whether young or old to being infected with swine flu or non swine flu (p>0.05). Table 2 also show that gender had no relation to possibility of infection with both non swine flu and swine flu influenza (P 0.05) and pneumonia are more commonly associate influenza of negative test for swine flu virus (p